DYNAMIC PROGRAM FOR DETERMINING SHORTEST TRACK APPROACH FLOYD-WARSHALL ALGORITHM - Enty Nur Hayati; Agus Setiawan (Jurnal Ilmiah Dinamika Teknik, 2013)
Lately journey optimum route search increasingly becomes an increasingly important issue triggered by rising fuel prices nearly doubled , so everyone trying to travel as quickly as possible to get to the destination with minimum cost . This study aims to determine the optimum route to the District of the District Ngaliyan Sampangan using Floyd Warshall algorithm that has the shortest distance assuming no constraints such as congestion and geographical circumstances of a lane of traffic on the route followed by the people who will make the trip and did not include element of the cost of the trip . Engineering approach used in the completion of this research program with the dynamic approach of Floyd - Warshall algorithm , which will choose the shortest path and the safest one of several alternative paths that have resulted from the process of calculation . From the results of the processing and analysis of data obtained that the optimal route for a trip from the area Kendeng Ngaliyan to generate the shortest distance 12 km route Ngaliyan ( A ) → Ngaliyan gas station ( B ) → Pasadena ( D ) → Kalipancur ( G ) → Simongan ( I) → Iron Bridge gas station ( K ) → Menoreh ( J ) → Kendeng ( L ) Keywords: dynamic program, Floyd-Warshall algorithm, stage, state, recursive functions